Strategy to Improve KPM’s Start-Up Business Creativity in the Context of Social Entrepreneurship Program - Yuce Sariningsih; Wanda Kiyah George Albert; Ine Mariane (Logos University International, 2023)
Purpose: The aim of this research was to investigate strategy to improve KPM’s start-up business creativity in the context of social entrepreneurship program. Theoretical framework: The primary goal of social work is to improve a society's overall well-being, especially for the most vulnerable populations. It's not just corporate responsibility where social workers can help businesses and strengthen entrepreneurship (Zastrow, 2017). Design/methodology/approach: The method used a qualitative approach by interviewing 3 informants of KPM, and the data was analysed by using SWOT analysis to helping identify competitive opportunities for improvement. It was designed to assess strengths (S) and weaknesses (W) as internal capabilities, while opportunities (O) and threats (T) are posed by the external environment. Findings: KPM was in incubate profile of creativity and need to empower their business skill to be sustainable, and needed the intervention of social work in giving some business education and to strengthen social entrepreneurship of KPM by using case work method should be improved. Research, Practical & Social implications: This research is urgently needed to break KPM's dependence on public assistance and increase their sustainable income through business startups and strengthen their entrepreneurial spirit. Originality/value: This research related to social work intervention in business and industry to strengthen KPM start-up through social entrepreneurship. KPM showed that they still rely on public assistance to meet their daily needs.